BRUSH FIBER COMPLAINTS ON THE USE OF SITTING AND STANDING WORK - Anizar; Muhammad Zainul Bahri Torong; Idhar Yahya (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Fiber brush production is entirely conducted manually by workers with the help of a very simple tool. Workers complain of experiencing pain in some parts of the body when working using sitting and standing postures. This study will evaluate the causes of pain complaints in workers who engage in fiber-binding and fiber-cutting activities. Pain complaints data are obtained from the Standard Nordic Questionnaire (SNQ) and work posture is assessed using the RULA and REBA methods. The assessment result shows that work method with unbalanced limb loadings induces pain complaints on workers. The choice between standing and sitting work posture is based on workload received by workers. Therefore, it is proposed to provide ergonomic work facilities in order to minimize the loading received by workers.